Improving a web-based employability intervention for work-disabled employees: results of a pilot economic evaluation. (3rd April 2017) - Noben, Cindy; Evers, Silvia; Genabeek, Joost van; Nijhuis, Frans; de Rijk, Angelique
Abstract: Purpose The purpose of this study is to improve web-based employability interventions for employees with work- related health problems for both intervention content and study design by means of a pilot economic evaluation.Methods Uptake rate analysis for the intervention elements, cost effectiveness, cost utility and subgroup analyses were conducted to identify potential content-related intervention improvements. Differences in work ability and quality-adjusted life years and overall contribution of resource items to the total costs were assessed. These were used to guide study design improvements.Results Sixty-three participants were a-select allocated to either the intervention ( n  = 29) or the control ( n  = 34) group. Uptake regarding the intervention elements ranged between 3% and 70%. Cost-effectiveness and cost-utility analyses resulted in negative effects although higher total costs. Incremental effects were marginal (work ability −0.51; QALY −0.01).Conclusions The web-based tool to enhance employability among work disabled employees requires improvements regarding targeting and intensity; outcome measures selected and collection of cost data. With respect to the studies of disability and rehabilitation, the findings and methods presented in this pilot economic evaluation could guide the assessment of future assistive "e-health" technologies. IMPLICATIONS FOR REHABILITATION: The methods presented in this pilot economic evaluation have large potentials to guide the assessment of future assistive e-health technologies addressing work-disabilities. The findings show that the web-based tool requires content related improvements with respect to targeting and intensity to enhance employability among work disabled employees. The findings show that the web-based tool would benefit from improvements related to the study design by more adequately selecting and collecting both outcome measures and cost data. The burden attributable to large-scale studies and implementation issues were prevented as the outcomes of the pilot economic evaluation did not support the implementation of the web-based tool.